Uterus didelphys with obstructed hemivagina and ipsilateral renal anomaly (OHVIRA syndrome): A case report - Mohamed Amin El-Gohary (Elsevier, 2014)
Uterus didelphys with obstructed hemivagina and ipsilateral renal anomaly (OHVIRA) syndrome is a rare congenital urogenital anomaly. We report a case of a 14-year-old female who presented with acute lower abdominal pain and tender pelvic mass. The initial diagnosis of twisted left ovarian cyst was confirmed by abdominal ultrasonography (US), which showed an associated absent left kidney. The findings at laparoscopy were that of uterus didelphys with obstructed left hemivagina. Parents were concerned about hymnal integrity and refused hemivaginal septal resection.